1997
DOI: 10.1042/bst0250717
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene therapy for cancer: herpes simplex virus thymidine kinase gene-mediated cell killing leads to anti-tumour immunity that can be augmented by co-expression of cytokines in the tumour cells

Abstract: Targeting Cytotoxic I m m u not he rapy compared with 7 for the conventional conjugate.This eliminates the need for a clearing antibody together with its immunogenicity. The problem of immunogenicity is diminished to that of CPG2, the variable region of MFE-23 and any novel epitopes at the junction of the antibody and enzyme.These preliminary studies indicate that such fusion proteins may have useful advantages over conventional reagents for targeted cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…A substantial literature exists on ectopic HSV1tk expression in animal models and human cancer therapy clinical trials, because of the potential ability to use HSV1tk as a therapeutic modality to locally activate prodrug acycloguanosines to toxic molecules. [23][24][25] As a result, we know more about ectopic expression of this reporter gene than other systems. Because HSV1tk is a 'foreign' gene, HSV1tk protein may be immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial literature exists on ectopic HSV1tk expression in animal models and human cancer therapy clinical trials, because of the potential ability to use HSV1tk as a therapeutic modality to locally activate prodrug acycloguanosines to toxic molecules. [23][24][25] As a result, we know more about ectopic expression of this reporter gene than other systems. Because HSV1tk is a 'foreign' gene, HSV1tk protein may be immunogenic.…”
Section: Discussionmentioning
confidence: 99%
“…39 The use of IL-2 and other cytokines in conjunction with HSVtk has also shown promise. 22 Thus, future advances that improve selective gene transfer will increase the power of this emerging therapy as an adjunctive or even primary treatment of many human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…24 Furthermore, co-expression of HSVtk and immunomodulatory genes may enhance the tumoricidal response in vivo. 22 In the present study, we hypothesized that human osteosarcoma in vitro and in athymic mice would be susceptible to gene therapy with HSVtk and IL-2. Two osteosarcoma cell lines, MNNG (a human osteosarcoma) and MLM (a human-derived osteosarcoma metastatic to murine lung), were transduced in vitro with the HSVtk, IL-2, or ␤-galactosidase (␤-gal) gene.…”
mentioning
confidence: 95%
“…Even though our animal model did not allow a thorough evaluation of the immune response, our in vivo results showed that GCV treatment of 50% transduced tumors led to a growth inhibition similar to the inhibition obtained in 100% infected tumors. The use of a cytokine gene besides a suicide gene allows the amplification of the antitumor effect by further stimulating immune-mediated rejection of cancer cells (13). Several in vivo studies in animal models of cancer demonstrated enhanced tumor cell killing with combined suicide and cytokine gene therapy (13 -18).…”
Section: Discussionmentioning
confidence: 99%